Plasmid-mediated verotoxin producing non-O157 Escherichia coli isolates from Malaysia - Khan, M. F. K.; Rashid, Shah Samiur; Maziz, M. N. H.; Aizi Nor Mazila, Ramli; Baharuddin, R. (International Society for Infectious Diseases, 2020)
Verocytotoxin producing Escherichia coli (VTEC) is not only the most frequent cause of diarrhea but also life-threating complications. A significant increase of verotoxin producing non-O157 E. coli (VTEC) infections has been represented as a serious public health concern due to its association with severe foodborne illness and outbreaks worldwide. These situations could be worsening through the dissemination of plasmid-mediated non-O157 VTEC worldwide. The aim of this study was to investigate the presence of plasmid-mediated verotoxin gene in non-O157 E. coli. Methods and materials: Forty-nine clinically significant verotoxins producing non-O157 E. coli were isolated from 137 stool specimens at Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. All the non-O157 VTEC isolates were identified using standard microbiological assays and confirmed by Polymerase Chain Reaction (PCR). Plasmids were isolated by Perfectprep Plasmid Mini preparation kit and subjected to disk diffusion assay, plasmid curing and molecular cloning in pGEM-T, and transformed into recombinant E. coli. The presence of plasmid-mediated verotoxin gene (VT1 and VT2) in recombinant E. coli was confirmed by colony PCR and Sanger sequencing. Results: Among the 49 clinical isolates of non-O157 VTEC, twenty-six (26) isolates were multi-drug resistant and possessed single sized plasmid while others had multiple plasmids with a different size varied from 1.2 kb to 7.5 kb. Of the total 26 plasmid harboring isolates, 11 isolates showed variation in susceptibility patterns while 3 isolates completely lost plasmids after post plasmid curing treatment. This observation was considered and encouraging as it suggested that the presence of the verotoxin gene could be plasmid-mediated. Polymerase chain reaction (PCR) derived DNA fragment containing the verotoxin gene of non-O157 E. coli was cloned into an expression vector. However, colony PCR and Sanger sequencing characterized 3 plasmids mediated VT1 (348 bp) and VT2 (584 bp) genes producing non-O157 E. coli. Conclusion: The occurrence of plasmid-mediated verotoxin gene producing non-O157 E. coli signify a serious public health issues on plasmid-mediated transmission of virulence genes. Public health surveillance and timely diagnosis of the emergence of plasmid-mediated verotoxin gene should be prioritized to avoid the dissemination of plasmid-mediated virulence gene transfer amongst the same bacteria or other species.